Dr. Alejandro Rayes — Deep Plane Facelift — Tijuana - Rayes, Alejandro (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Alejandro Rayes, practicing in Tijuana, Mexico. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-002991; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; mexico; tijuana